Structural gene for the alkaline extracellular protease of Saccharomycopsis lipolytica. - Simms, P C (1981)
Mutants for Saccharomycopsis lipolytica temperature sensitive for alkaline extracellular protease production, but not for growth, were isolated. Thirty-three isolates were temperature sensitive for protease production, and one (xpr-32) produced a temperature-sensitive protease. Genetic analysis indicated that xpr-32 was located in gene XPR2, and allele xpr2-7 was found to also produce a temperature-sensitive protease. None of five independently isolated xpr2 mutations affects the production of extracellular ribonucleases and acid protease(s). Diploids with zero, one, or two active alleles of the XPR2 locus were constructed, and the XPR2 locus was shown to exhibit a gene dosage effect on alkaline extracellular protease synthesis (enzyme activity/cell protein). These results suggest that the XPR2 gene is the structural gene for the alkaline extracellular protease of S. lipolytica.